PEMBENTUKAN KARAKTER KRISTIANI ANAK MELALUI METODE CERITA ALKITAB INTERAKTIF - Nurhayati Sitorus; Tioma Lasti Marito Simamora; Eva Susilawati Nainggolan; Mey Syafitri Manalu; Sindy Mastuty Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Character development in kindergarten children is crucially determined by an appropriate and effective learning system. An appropriate and effective learning system is a learning approach tailored to their development. In this context, this activity was implemented through Community Service (PkM) at the HKBP Tarutung Kindergarten, using the interactive Bible story method as a means of instilling Christian values. This method was chosen because it actively engages children through fun and communicative activities. The activity encompasses planning, implementation, and evaluation, conducted through observation and direct interaction with the HKBP Kindergarten children.The results of the PkM activity indicate that the approach implemented was able to encourage and develop children's understanding of Christian values, particularly those encompassing love, honesty, obedience, and responsibility, becoming clearer and more nuanced. Furthermore, there was an increase in children's participation, discipline, and social skills during the learning activities. This demonstrates that the interactive Bible story method is effective in supporting the gradual character development of kindergarten children.